2006
DOI: 10.3748/wjg.v12.i8.1249
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and inter-observer variability for capsule endoscopy image analysis in a cohort of novice readers

Abstract: sensitivity in detecting lesions on capsule endoscopy. A group of novice readers can pre-screen recordings to thumbnail potential areas of small bowel lesions for further review. These thumbnails must be reviewed to determine the clinical relevance. Further studies are ongoing to assess other cohorts. INTRODUCTIONCapsule endoscopy is a new diagnostic procedure developed for the complete examination of the small intestine through video images transmitted from an ingestible camera [1][2][3] . Briefly, the PillC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 21 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…However, there is increasing awareness within diagnostic and therapeutic specialties that proficiency should be based on competency rather than numbers performed, especially as lesion recognition skills are often neglected as part of endoscopic training. While published studies have demonstrated that non-experts without prior CE training (medical students, technicians, and endoscopy nurses) may identify 30-100% of lesions detected by an expert [18,22], there is no literature to date that outlines the appropriate type or amount of CE training required to achieve competent independent practice. This preliminary study is the first to assess changes in performance during a ''hands-on'' CE training program such as might be used in everyday practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is increasing awareness within diagnostic and therapeutic specialties that proficiency should be based on competency rather than numbers performed, especially as lesion recognition skills are often neglected as part of endoscopic training. While published studies have demonstrated that non-experts without prior CE training (medical students, technicians, and endoscopy nurses) may identify 30-100% of lesions detected by an expert [18,22], there is no literature to date that outlines the appropriate type or amount of CE training required to achieve competent independent practice. This preliminary study is the first to assess changes in performance during a ''hands-on'' CE training program such as might be used in everyday practice.…”
Section: Discussionmentioning
confidence: 99%
“…The cost-effectiveness of the capsule endoscopy study in the evaluation of patients with obscure GI bleeding may be increased by the preview of the recordings by an endoscopy nurse or an assistant. [107][108][109] In a pilot study by Appleyard et al in 2000, radioopaque beads were sewn into canine small bowels to compare the diagnostic yield between push enteroscopy and capsule endoscopy. Capsule enteroscopy identified more beads overall (64%) compared with push enteroscopy (37%), although push enteroscopy was found to be more sensitive for bead detection in the first meter of the examination (94% compared with 53% for capsule).…”
Section: Investigationsmentioning
confidence: 99%
“…Six studies were excluded for the following reasons: two did not involve nurses; 18,19 one used a bowel model instead of actual patients; 20 two used QuickView to aid CE reading; 21,22 and one did not have an adequate reference standard to gauge performance of the nurse endoscopist, as an inexperienced nurse was compared to a physician also inexperienced in CE. 11…”
Section: Resultsmentioning
confidence: 99%